2021
DOI: 10.3390/su132413681
|View full text |Cite
|
Sign up to set email alerts
|

Green Hydrogen Value Chain in the Sustainability for Port Operations: Case Study in the Region of Valparaiso, Chile

Abstract: The paper presents a complete value chain for the use of green hydrogen in a port facility. The main objective was to propose the sizing of the main components that make up green hydrogen to ensure the supply of 1 MWe in replacing the diesel generator. The energy demand required for the port was determined by establishing the leading small and large-scale conventional energy-consuming equipment. Hence, 60 kgH2 was required to ensure the power supply. The total electrical energy to produce all the hydrogen was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In the article (Masip Macía et al, 2021), a whole value chain for using green hydrogen in port facilities is shown. The major goal was to suggest the sizing of the primary green hydrogen components in order to guarantee a supply of 1 MWe in order to replace the diesel generator.…”
Section: Problem Statementmentioning
confidence: 99%
“…In the article (Masip Macía et al, 2021), a whole value chain for using green hydrogen in port facilities is shown. The major goal was to suggest the sizing of the primary green hydrogen components in order to guarantee a supply of 1 MWe in order to replace the diesel generator.…”
Section: Problem Statementmentioning
confidence: 99%
“…The complexity of a hydrogen production, storage, and delivery system in a port depends on the production method used (for example, green hydrogen from renewable energy sources), the type of application (whether the hydrogen is used for fuel cell vehicles), and the specific characteristics of the port [31,32]. A techno-economic analysis of hydrogen production in the port of Trieste has been carried out, considering on the one hand the demand for hydrogen fuel in the steel works of the port and on the other hand the case of fuelling a steel works and a hydrogen fuelling station in the port.…”
Section: Alternative Fuelsmentioning
confidence: 99%
“…Operational values fall within existing limits for power plants, including those utilizing fossil fuels. When considering the ratio between investment capital and operational costs relative to the electric power produced by installations using renewable sources and stored in green hydrogen, specific values can be identified [22,23]. If you add the investment related to compression and storage (which can be of various technologies), along with that related to buildings, power lines, etc., you reach very high values, around 7000-8500 USD/(kW), with much over the investment in other electricity production systems or even its storage by using other technologies.…”
Section: The Concept and Process Of Storing Electric Energy From Rene...mentioning
confidence: 99%